Semiconductor wireless technology for chronic disease management - Tarassenko, L; Clifton, D (IEEE, 2011)
With most chronic diseases, monitoring of one or more physiological variables (vital signs) can inform the management of the patient. In active monitoring, the patient adjusts medication dosage according to the value of the measured variable. Passive monitoring is associated with the more advanced stages of chronic diseases and requires the use of wearable sensors. 'Digital plasters' which exploit recent advances in semiconductor technology can now provide continuous monitoring and wireless transmission of patients' vital signs for several days. The ideal digital plaster, or adhesive patch, for long-term passive monitoring would incorporate both electrical and optical measurements. Other promising technologies for the future include implantable sensors and non-contact vital sign imaging.